Politeness Strategies and Gender Differences in the Speech Act of Rejection among the Malays in Malaysia - Che Ismail, Nur Asyrani binti (Association of Language Teachers in Southeast Asia (ALTSA), 2018)
Men and women utilise language to serve various purposes. Making rejection falls as one of the functions through which gender differences in the language may be identified. Research seems to suggest that men and women construct and incorporate politeness differently while performing speech acts of rejection. Therefore, this study aims to identify the positive and the negative politeness strategies that both genders use in making a rejection and also to compare, to what extent politeness strategies of males differ from those of females in making rejection. This study employs the framework of Brown and Levinson’s Model of Politeness (1987) where it is realised through a set of questionnaire involving nine different situations and is formulated based on an oral Discourse Completion Task. The oral DCT is tested on 50 male and 50 female students of International Islamic University Malaysia. As a whole, males use more positive and negative politeness strategies than females when making rejections. While in a broader context, both genders are generally explanative and apologetic when making rejections. Therefore, this study is able to suggest better ways for society members in the future on how to make appropriate rejections to each other.